DHT-based cluster routing protocol for IEEE802.11s mesh networks - Marcos Pinheiro (2009)
The IEEE 802.11s draft standard defines a mesh network in which frame delivery is done by forwarding the frame through nodes, called Mesh Points (MPs). To make this possible, it specifies two routing protocols: HWMP and RA-OLSR. Both protocols suffer from scalability issues caused by the use of broadcast messages for discovery and update of routes. In this work, we propose a new routing protocol, the DHT-based Cluster Routing Protocol (DCRP), that improves the scalability of 802.11s networks. Our approach is based on two mechanisms: clustering of nodes and IN-IT-based searching. Clustering allows to reduce the number of broadcast messages required for routing as well as the amount of routing information broadcasted. DHT-based searching is used to make up for the required routing information that is not diffused by the DCRP itself. Some back-of-the-envelope calculations indicate that our approach increases the scalability of the routing protocol.